Removal of Pyrene from Aqueous Solution Using Fe-based Metal-organic Frameworks - Zango, Z.U. (IOP Publishing Ltd, 2020)
Metal-organic frameworks (MOFs), MIL-88(Fe) and NH2-MIL-88(Fe) were synthesized using microwave-assisted solvothermal technique. BET analysis has shown the porous nature of the MOFs, possessing surface areas with corresponding pore volumes of 1240 m2g-1 and 0.7 m3 g-1, 941 m2 g-1 and 0.6 m3 g-1 for MIL-88(Fe) and NH2-MIL-88(Fe), respectively. Other characterizations were also conducted using scanning electron microscopy (SEM), powdered X-ray diffraction (XRD) and Fourier transformed infrared (FTIR) spectroscopy. The MOFs were evaluated for application as adsorbents for the removal of pyrene (PYR) in aqueous solution. The removal efficiency achieved by MIL-88(Fe) was 99.7 while for NH2-MIL-88(Fe) was 96.0 within 40 minutes. Both MOFs has shown good removal of the PYR even after 5 consecutive uses. The adsorption isotherm was studied and favoured more by the Langmuir model, while the kinetics was found to follow pseudo-second-order model. The process was thermodynamically exothermic and spontaneous. Thus, the MOFs studied exhibited favourable features as potential adsorbents for the removal of PYR in wastewater. Â© Published under licence by IOP Publishing Ltd.